Garden Paintings of Pompeii: Context and Meaning - Kane, Tanya (My University, 1998)
Garden paintings are ubiquitous in Campanian wall painting. This thesis examines the garden compositions of Pompeii. Despite the large number of well-preserved garden frescoes, these scenes have received relatively little attention from modem scholars. Yet following the earthquake of 62 A.D. they were among the first elements to be repaired by the inhabitants of Pompeii. Furthermore, due to the ephemeral nature of real gardens, garden paintings provide valuable information about the typical plantings, landscaping, decoration, and furnishings found in ancient viridaria.
Chapter 1 surveys the gardens and depictions of gardens found in the vicinity of Rome, including funerary gardens, market gardens, private imperial gardens, and public horti. Garden paintings from Livia's Villa at Prima Porta, the Auditorium of Maecenas, the Domus Publica, the Farnesina House, and the Tomb of Patro are discussed in this chapter.
Chapter 2 gives a detailed description of the types of features and decorations found in the real gardens of Pompeii. Important background information regarding the source of inspiration of garden paintings is conveyed by outlining the characteristic elements of private gardens.
Chapter 3 enumerates and discusses the basic elements found in garden compositions. The elements are divided into three separate and distinct categories, namely architectural elements, decorative elements, and flora and fauna.
The composition of garden paintings is examined in Chapter 4. The arrangement of the constituent elements, such as lines, colours, and shapes comprises the main focus of this analysis.
Chapter 5 deals with the placement of garden paintings within domestic settings. Trends, such as the tendency to place verdant scenes in certain types of rooms and in conjunction with specific thematic programs, are identified in this chapter.
The discussion of the final chapter revolves around the possible functions of garden paintings. Specific roles were assigned to garden paintings in indoor and outdoor contexts.
Keywords: Classics; Classics